The Chinatown and The Rise of Ethnical Violence During Pandemic in the US: The Responses of International Cultural and Social Policy - M Solahudin Al Ayubi; Kalyana Almira Benedicta; Shafa Auli Ramadhanti; Fatimah Az Zahra (AEGIS : Journal of International Relations, 2022)
Chinatown is a residential area inhabited by a group of ethnic Chinese. These settlements have been widely spread in various countries since hundreds of years ago and attracted the tourist all over the world. Nevertheless, the emergence of COVID-19 pandemic since 2019 has affected the existence of Chinatown as well as the increase of ethnical violence “Asian hates” in US. The purpose of this research is to analyze the implications COVID-19 toward the Chinatown and the rise of ethnical violence. Hence, the response of international cultural and social policy will be the framework in analyzing the phenomenon. This research uses descriptive-qualitative method that mostly collects secondary data such as books, journals, newspapers, magazines, news portals, articles, official websites, and so on. Through this method, the research found that the COVID-19 has significantly affected the rise of ethnical violence in most of the Chinatown in the US. However, the international cultural and social policy has responded that the COVID-19 is not only affecting the health sector yet also the social and cultural sector. The fact that cultural and social sector are vulnerable in pandemic situation should obtain the attention from various stakeholders including government and their policies. Furthermore, there are alternative strategies – cultural and social policy approach to prevent the increase number of ethnical violence occurred, especially for the future pandemic.